Respuesta :

To factor out -1/3 out of the expression -1/3x - 8, first divide -8 by -1/3 to get 24. Now just put 24 in the place of -8 in the original expression. Your final answer should be -1/3(x + 24). Hope this helps and have a phenomenal day!

Answer:

The factor form is [tex]-\frac{1}{3}x-8=-\frac{1}{3}(x+24)[/tex]

Step-by-step explanation:

To find : Factor [tex]-\frac{1}{3}[/tex] out of [tex]-\frac{1}{3}x-8[/tex]

Solution :

Taking the term common means we the number multiply inside give you the same result.

Taking [tex]-\frac{1}{3}[/tex] out of [tex]-\frac{1}{3}x[/tex] is left with

[tex]\frac{-\frac{1}{3}x}{-\frac{1}{3}}=x[/tex]

Taking [tex]-\frac{1}{3}[/tex] out of [tex]8[/tex] is left with

[tex]\frac{8}{-\frac{1}{3}}=-8\times 3=-24[/tex]

So, [tex]-\frac{1}{3}x-8=-\frac{1}{3}(x-(-24))[/tex]

[tex]-\frac{1}{3}x-8=-\frac{1}{3}(x+24)[/tex]

The factor form is [tex]-\frac{1}{3}x-8=-\frac{1}{3}(x+24)[/tex]